Literasi Generasi Z Mengenai Kejahatan Cybercrime di Media Sosial - Nurul Azmi; Cindi Pricilia; Zaskia Dyayu Larasati; Auzora Vidya Nataha (Asosiasi Dosen Akuntansi Indonesia, 2025)
This study aims to measure the level of digital literacy among Generation Z towards cybercrimes on their social media, such as phishing, scamming, and account hacking. This research uses a quantitative method through an online questionnaire survey distributed to 50 individuals who belong to Generation Z in Pekanbaru. The data were processed by calculating the mean, median, percentage, and others, and analyzed with descriptive narratives. The results of this study show that the majority of the total respondents already understand and have an awareness of the importance of maintaining the security of personal information on social media. They have shown positive actions towards the use of personal information security, such as creating passwords that are not easy to guess, being careful in accepting friendships on social media, and knowledge of cybercrime terms. However, there is still a gap between attitudes and actions, such as some respondents saying that they are aware of cybercrime, but they still do things that make cybercrime risks occur, such as rarely updating account security settings.